Financial Ratios as a Powerful Instrument to Predict Insolvency; a Study Using Boosting Algorithms in Colombian Firms (2020)
RESUMEN: This study is motivated by the importance of accurately predicting insolvency before it happens. The paper aims to develop an insolvency prediction model for Colombian firms with one, two and three years of anticipation through financial ratios, keeping sample structures and taking into account insolvency-related regulation. This research contributes to the literature because unlike many studies, it takes legislation into account, explains the different types of financial ratios, and uses boosting algorithms without biasing the sample. Data from 11,812 Colombian companies covering the period 2012-2016 was used. The results show accuracy above 70% for insolvency prediction with one, two and three years of anticipation. RESUMEN: Esta investigación es motivada por la importancia de tener una buena predicción de la insolvencia con anticipación. El objetivo de este artículo es desarrollar un modelo predictivo para las empresas colombianas con uno, dos y tres años de anticipación usando indicadores financieros, conservando la estructura de la muestra original y teniendo en cuenta la regulación sobre insolvencia. Este artículo contribuye a la literatura ya que, a diferencia de los estudios tradicionales, se tienen en cuenta aspectos como la legislación, se explican los diferentes tipos de indicadores financieros y se utiliza el algoritmo boosting sin sesgar la muestra inicial. Para el desarrollo de este estudio se consideró una muestra de 11.812 empresas colombianas durante el periodo 2012.